If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -3t = 4t + -34 Reorder the terms: 15 + -3t = -34 + 4t Solving 15 + -3t = -34 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 15 + -3t + -4t = -34 + 4t + -4t Combine like terms: -3t + -4t = -7t 15 + -7t = -34 + 4t + -4t Combine like terms: 4t + -4t = 0 15 + -7t = -34 + 0 15 + -7t = -34 Add '-15' to each side of the equation. 15 + -15 + -7t = -34 + -15 Combine like terms: 15 + -15 = 0 0 + -7t = -34 + -15 -7t = -34 + -15 Combine like terms: -34 + -15 = -49 -7t = -49 Divide each side by '-7'. t = 7 Simplifying t = 7
| 4w+4x-12y+5w+7x+4y= | | 5x^3+4=2 | | 10h+4=10 | | 15x-28y=1 | | 5(6p)=3(8p-4) | | 10z-5(z+3)= | | 4y-12=12+4y | | Y(2y+5)=52 | | 22+7=5 | | 22+5=5 | | 3y^4=6 | | 3(x+9)=4(2x+2) | | 5x^2+2=3 | | 2e=0 | | (3g+8)(2g-4)= | | 7x-5+4x+4=3x+5+8x-6 | | 6(H-14)+2(H-3)=14 | | 6x^2-3x=-18 | | 3(x+9)=4(2x+1) | | (x+9)=2*4(x+1) | | 3(x+9)=8(x+1) | | 21/3×3 | | p/300-185 | | 4*g=36 | | 11/5-3/10 | | 2(X-6)=19 | | 4z-6=7 | | (x-5)=3x+4 | | f(x-5)=3x+4 | | D=10-(3a-5)+(9+3a) | | y=9mx+7 | | t/3-4=11 |